2020
DOI: 10.3390/ph13090220
|View full text |Cite
|
Sign up to set email alerts
|

Future of Chondroprotectors in the Treatment of Degenerative Processes of Connective Tissue

Abstract: Osteoarthritis is one of the most common diseases of the connective tissue of the elderly. It was found that most epidemiological studies used the Kellgren and Lawrence system for classification of osteoarthritis, which indicates one of the 5 degrees (0–4) of osteoarthritis in various joints according to the radiographic atlas. It has been proven that chondroprotectors are represented by the following active substances: chondroitin sulfate, glucosamine sulfate or hydrochloride, hyaluronic acid, glycosaminoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
1
19
0
2
Order By: Relevance
“…In proteomics analysis of osteoarthritis patient-derived chondrocytes, ex-vivo chondroitin sulfate supplementation mainly resulted in remodeling of extracellular proteins and some inflammatory-associated proteins ( Calamia et al, 2012a ). This is consistent with many animal and human studies showing that chondroitin sulfate supplementation inhibits cartilage destruction and stimulates proteoglycan production for bolstering the connective tissues ( Bassleer et al, 1998 ; Omata et al, 2000 ; Tahiri et al, 2007 ; Huskisson, 2008 ; Taniguchi et al, 2011 ; Martel-Pelletier et al, 2015 ; Sukhikh et al, 2020 ). Taken together, supplementing with chondroitin sulfate tips the balance towards prolonged extracellular matrix protein homeostasis, a requisite for healthy aging ( Figure 1 ).…”
Section: Potential Mechanisms Promoted By Chondroitin Sulfatesupporting
confidence: 90%
“…In proteomics analysis of osteoarthritis patient-derived chondrocytes, ex-vivo chondroitin sulfate supplementation mainly resulted in remodeling of extracellular proteins and some inflammatory-associated proteins ( Calamia et al, 2012a ). This is consistent with many animal and human studies showing that chondroitin sulfate supplementation inhibits cartilage destruction and stimulates proteoglycan production for bolstering the connective tissues ( Bassleer et al, 1998 ; Omata et al, 2000 ; Tahiri et al, 2007 ; Huskisson, 2008 ; Taniguchi et al, 2011 ; Martel-Pelletier et al, 2015 ; Sukhikh et al, 2020 ). Taken together, supplementing with chondroitin sulfate tips the balance towards prolonged extracellular matrix protein homeostasis, a requisite for healthy aging ( Figure 1 ).…”
Section: Potential Mechanisms Promoted By Chondroitin Sulfatesupporting
confidence: 90%
“…Hyaluronic acid (HA) is a macromolecule from a natural source, widely used in biomedical applications due to its good biocompatibility, biodegradability, and low toxicity, especially in cosmetics, treatments for arthritis, and drug delivery [ 19 , 20 , 21 , 22 , 23 , 24 ]. Recent studies have demonstrated that the surface of cancer cells over-express the CD44 receptors on their surface, to which HA strongly binds [ 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…If the regenerative effects proven by studies [21,24] can be expanded on periodontal lesions, we expect Alflutop ® therapy to have a long-term stimulation effect on the alveolar bone's regeneration, but this will be a subject of future research. It has been shown that biomaterials for the periodontal ligament and bone regeneration provide good results in terms of maintaining bone volume, also offering a high percentage of vitality, safety, and lack of complications [24,26,31].…”
Section: Discussionmentioning
confidence: 99%